Pertumbuhan dan Produksi Tanaman Padi Varietas Inpara-3 pada Tanah Tergenang yang Diberikan Abu Batubara - Muhammad Helmy Abdillah; Akhmad Rizalli Saidy; Raihani Wahdah (Rawa Sains: Jurnal Sains STIPER Amuntai, 2020)
Paddy cultivation in South Kalimantan is a priority activity undertaken by various parties to create national food security and make Indonesia a world food barn in 2045. Increasing paddy production can always be supported by various supports, marginal swamp investment with various limiting soil fertility and strive for it to be planted with superior paddy varieties. The purpose of this study is to try to utilize ameliorant from coal fuel (fly ash) added to from three soil typology as swampy wetlands, tidal lands, and peat soils to improve the performance and growth of paddy varieties in Inhibrida Padi Rawa 3 (INPARA-3). This study uses a Completely Randomized Design in models nested factorial, using the application of fly ash given to each typology of the soil obtained. This research was conducted at the Greenhouse Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru, South Kalimantan. Giving fly ash in each type of soil is carried out by its bulk density. Fly ash given is 60 t.ha-1which is converted to 309.36 grams in each polybag of soil for soils from swampy land, 374.52 grams in each polybag soil for soil from tidal swamps and 519.56 grams in each polybag peat soil. From the analysis of the growth and production performance of paddy, planted on peat soils given fly ash, showed positive results on all parameters discussed, but different from the performance and growth of paddy that was planted on the ground from the soil, tides are given fly ash, only showed positive results on plant parameters height, height increase, number of tillers, grain dry weight, and longest roots of paddy. Analysis of growth and production performance was also carried out on paddy in the soil from swampy land, it appeared positive only on the parameters of grain dry weight, plant dry weight (without roots, panicles, and grain).